Cryogenian evolution of stigmasteroid biosynthesis - Hoshino, Yosuke; Poshibaeva, Aleksandra; Meredith, William; Snape, Colin; Poshibaev, Vladimir; Versteegh, Gerard J.M.; Kuznetsov, Nikolay; Leider, Arne; van Maldegem, Lennart; Neumann, Mareike; Naeher, Sebastian; Moczydłowska, Małgorzata; et al. (American Association for the Advancement of Science, 2017)
Sedimentary hydrocarbon remnants of eukaryotic C26–C30 sterols can be used to reconstruct early algal evolution. Enhanced C29 sterol abundances provide algal cell membranes a density advantage in large temperature fluctuations. Here, we combined a literature review with new analyses to generate a comprehensive inventory of unambiguously syngenetic steranes in Neoproterozoic rocks. Our results show that the capacity for C29 24-ethyl-sterol biosynthesis emerged in the Cryogenian, that is, between 720 and 635 million years ago during the Neoproterozoic Snowball Earth glaciations, which were an evolutionary stimulant, not a bottleneck. This biochemical innovation heralded the rise of green algae to global dominance of marine ecosystems and highlights the environmental drivers for the evolution of sterol biosynthesis. The Cryogenian emergence of C29 sterol biosynthesis places a benchmark for verifying older sterane signatures and sets a new framework for our understanding of early algal evolution.